Pengaruh waktu vulkanisasi terhadap kuat rekat antara foksing dengan kanvas pada sepatu kanvas untuk umum - Sri Nadilah; Penny Setyowati; Murwati Murwati (Majalah Kulit, Karet, dan Plastik, 1994)
Determination of curing condition at cemented process for canvas shoes vulcanization system is an important factor for producing optimal cemented strength value. Short curing gives low cemented strength value since latex or rubber compound is imperfect vulcanized. Long curing also gives low cemented strength value since a part of latex or rubber compound has got degradation. The research is carried out to obtain optimal curing time in order to obtain the highest cemented strength value. The glue applied is latex with operation condition steam vulcanization : chamber temperature 90 - 100oC, steam pressure 2,0 – 2,5 kg/cm2 variation time 30,40 and 50 minutes. Vulcanization product is tested for its cemented strength with the higest result 18,224 N/6 mm for 40 minutes curing time. The result fulfills specification SII. 1407 - 85 "Sepatu Kanvas Untuk Umum".